Leukobiopsy – A Possible New Liquid Biopsy Platform for Detecting Oncogenic Mutations - Chennakrishnaiah, Shilpa; Tsering, Thupten; Aprikian, Saro; Rak, Janusz (Frontiers in Pharmacology, 2020)
Detection of unique oncogenic alterations encoded by the sequence or biochemical modification in cancer-associated transforming macromolecules has revolutionized diagnosis, classification and management of human cancer. While these signatures were traditionally regarded as largely intracellular and confined to the tumour mass, oncogenic mutations and actionable cancer-related molecular alterations can also be accessed remotely through their recovery from biofluids of either rare circulating tumour cells (CTCs), or of more abundant non-cellular carriers, such as extracellular vesicles (EVs), protein complexes, or cell-free tumour DNA (ctDNA). Tumour-related macromolecules may also accumulate in circulating platelets. Collectively, these approaches are known as liquid biopsy and hold promise as non-invasive, real-time opportunities to access to the evolving molecular landscape of human cancers. More recently, a possibility of recovering cancer-specific DNA sequences from circulating leukocytes has also been postulated using experimental models. While it is often assumed that these and other liquid biopsy approaches rely on material passively shed from the tumour mass or its debris, recent evidence suggests that several regulated processes contribute to the abundance, nature, half-life and turnover of different circulating cancer-related molecular signals. Moreover, many of these signals possess biological activity and may elicit local and systemic regulatory responses. Thus, a better understanding of the biology of liquid biopsy platforms and analytes may enable achieving improved performance of this promising and emerging diagnostic strategy in cancer.